Puzzle Town - Susannah Leigh (England Usborne Publishing Ltd, 1991)
- Entertaining stories filled with lots of fun picture-puzzles -- Large pages with full-color cartoon style artwork coupled with exciting, fantastical adventures
Keywords: Everything sports - Recreational Activities -- Everything sports - Recreational Activities